Simulation study on impact characteristics of RF microsystem based on bulk silicon MEMS process - Feng Zhengsen; Wang Lu; Zeng Yanping; Yang Bing; Qi Dong; Wang Zhihui; Zhang Rui (Dianzi Jishu Yingyong)
The high overload impact test is costly and time consuming, and the failure detection means are few, so it is difficult to locate the weak points of the structure. In this paper the impact response spectrum and transient dynamics method are used to study the impact load response of a RF microsystem based on bulk silicon micro-electromechanical system(MEMS) at plate level and under experimental conditions. The simulation results show that the RF microsystem can bear a high impact load，which can predict the structural failure point so as to improve the impact reliability of product.